FALSE TENDONS IN THE LEFT VENTRICLE - F. A. Blyakhman; Yu. A. Zinovieva; K. R. Mekhdieva; A. M. Naydich; S. Yu. Sokolov; V. E. Timokhina (Российский кардиологический журнал)
Aim. To find out the close mean-end relations of the false tendons (FT) topology in the left ventricle (LV), regional and global heart functioning, including its ability to endure exertion.Material and methods. Totally, 90 healthy young persons included (48 females), age 20,2±2,9 y.o., actively participating in sports. Connective tissue dysplasia was confirmed according to National guidelines on Diagnostics and management of inherited connective tissues disorders (2012). The routine echocardiographic study was done with further digital processing and 3D modelling of the LV with regional myocardium function assessment. The ability of the heart to adapt exertion was measured by exercise test on thread-mill.Results. Describing of FT topology in 3D-model of LV revealed the presence of 1 to 5 tendons by 1 LV, which mostly were located in upper parts of the ventricle, and oriented perpendicularly or at small angle to its longitudinal axis. Main values of global structure and function of the LV were at normal range, but in all participants, there was high level of mechanical asynchronicity at rest. In addition, there was high variability of parameters related to the ability of the heart to endure exercises. By methods of correlational, monofactorial and multifactorial analysis, it was revealed that: as many FT by 1 LV, as higher the level of baseline mechanical asynchronicity and lower the heart ability to adapt exertion.Conclusion. Young healthy persons with FT in LV, participating systematically in sports, physical exercise or fitness, need strictly individualized regimen of exercise.